Docking‐based generation of antibodies mimicking Cry1A/1B protein binding sites as potential insecticidal agents against diamondback moth (Plutella xylostella). Issue 10 (23rd June 2021) - Xie, Yajing; Xu, Chongxin; Gao, Meijing; Zhang, Xiao; Lu, Lina; Hu, Xiaodan; Chen, Wei; Jurat‐Fuentes, Juan L; Zhu, Qing; Liu, Yuan; Lin, Manman; Zhong, Jianfeng; et al.
Abstract: BACKGROUND: Broad use of insecticidal Cry proteins from Bacillus thuringiensis in biopesticides and transgenic crops has resulted in cases of practical field resistance, highlighting the need for novel approaches to insect control. Previously we described an anti‐Cry1Ab idiotypic‐antibody (B12‐scFv) displaying toxicity against rice leafroller ( Cnaphalocrocis medinalis ) larvae, supporting the potential of antibodies for pest control. The goal of the present study was to generate insecticidal antibodies against diamondback moth ( Plutella xylostella ) larvae. RESULTS: Four genetically engineered antibodies (GEAbs) were designed in silico from B12‐scFv using three‐dimensional (3D) structure and docking predictions to alkaline phosphatase (ALP) as a Cry1Ac receptor in P. xylostella . Among these GEAbs, the GEAb‐dVL antibody consisting of two light chains had overlapping binding sites with Cry1A and Cry1B proteins and displayed high binding affinity to P. xylostella midgut brush border membrane (BBM) proteins. Proteins in BBM identified by pull‐down assays as binding to GEAb‐dVL included an ABC transporter and V‐ATPase subunit A protein. Despite lacking the α‐helical structures in Cry1A that are responsible for pore formation, ingestion of GEAb‐dVL disrupted the P. xylostella larval midgut epithelium and resulted in toxicity. Apoptotic genes were activated in gut cells upon treatment with GEAb‐dVL . CONCLUSION: This study describes the first insecticidal GEAb targeting P. xylostella by mimicking Cry proteins. Data support that GEAb‐dVL toxicity is associated to activation of intracellular cell death pathways, in contrast to pore‐formation associated toxicity of Cry proteins. This work provides a foundation for the design of novel insecticidal antibodies for insect control. © 2021 Society of Chemical Industry. Abstract : Here describes the generation of first insecticidal genetically engineered antibody (GEAb‐dVL ) against P. xylostella larvae, which mimics Cry proteins in binding to midgut brush border membrane and disrupting gut epithelium.